2006
DOI: 10.1111/j.1440-1746.2005.04003.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal gastroesophageal flap valve is highly associated with gastroesophageal reflux disease among subjects undergoing routine endoscopy in Taiwan

Abstract: Taiwanese patients with abnormal GEFVs share similar characteristics and risk factors with the patients who have EE. Endoscopic grading of the GEFV is highly associated with GERD, and in particular EE, in subjects undergoing routine endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
3
17
1
1
Order By: Relevance
“…Although the presence of intestinal metaplasia was not assessed in ESEM, the presence of ESEM is a necessary condition for the development of Barrett's esophagus. These findings are consistent with previous reports showing that an abnormal GEFV is associated with reflux esophagitis and Barrett's esophagus 11,25–27 …”
Section: Discussionsupporting
confidence: 94%
“…Although the presence of intestinal metaplasia was not assessed in ESEM, the presence of ESEM is a necessary condition for the development of Barrett's esophagus. These findings are consistent with previous reports showing that an abnormal GEFV is associated with reflux esophagitis and Barrett's esophagus 11,25–27 …”
Section: Discussionsupporting
confidence: 94%
“…Prior studies in adults have also demonstrated similar findings [16], [25], [26]. The present study is the first report to confirm the relationship between altered GEFV grading and prevalence of erosive esophagitis in children.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the length of the hernia seems to affect the severity of GERD [19]. [21,22]. Interestingly, Takeuchi et al found that GEFV grade could predict the appearance of a newly developing esophagitis after Helicobacter pylori eradication [23].…”
Section: Discussionmentioning
confidence: 97%